Are morphological and structural MRI characteristics related to specific cognitive impairments in neurofibromatosis type 1 (NF1) children?. (September 2020) - Baudou, Eloïse; Nemmi, Federico; Biotteau, Maëlle; Maziero, Stéphanie; Assaiante, Christine; Cignetti, Fabien; Vaugoyeau, Marianne; Audic, Frederique; Peran, Patrice; Chaix, Yves
Abstract: Introduction: NF1 children have cognitive disorders, especially in executive functions, visuospatial, and language domains, the pathophysiological mechanisms of which are still poorly understood. Materials and methods: A correlation study was performed from neuropsychological assessments and brain MRIs of 38 NF1 patients and 42 controls, all right-handed, aged 8–12 years and matched in age and gender. The most discriminating neuropsychological tests were selected to assess their visuospatial, metaphonological and visuospatial working memory abilities. The MRI analyses focused on the presence and location of Unidentified Bright Objects (UBOs) (1), volume analysis (2) and diffusion analysis (fractional anisotropy and mean diffusivity) (3) of the regions of interest including subcortical structures and posterior fossa, as well as shape analysis of subcortical structures (4). The level of attention, intelligence quotient, age and gender of the patients were taken into account in the statistical analysis. Then, we studied how diffusion and volumes parameters were associated with neuropsychological characteristics in NF1 children. Results: NF1 children present different brain imaging characteristics compared to the control such as (1) UBOs in 68%, (2) enlarged total intracranial volume, involving all subcortical structures, especially thalamus, (3) increased MD and decreased FA in thalamus, corpus callosum and hippocampus. These alterations are diffuse, without shape involvement. In NF1 group, brain microstructure is all the more altered that volumes are enlarged. However, we fail to find a link between these brain characteristics and neurocognitive scores. Conclusion: While NF1 patients have obvious pathological brain characteristics, the neuronal substrates of their cognitive deficits are still not fully understood, perhaps due to complex and multiple pathophysiological mechanisms underlying this disorder, as suggested by the heterogeneity observed in our study. However, our results are compatible with an interpretation of NF1 as a diffuse white matter disease. Highlights: Diffuse enlarged brain volumes are a brain characteristic in NF1 children. In NF1 children's brain, diffusion parameters are not only altered in UBOs. Diffusion and volumetric parameters are particularly altered in thalamic regions. Specific cognitive features of NF1 children are not correlate with brain imaging. Our results are in accordance with the hypothesis of a looser packing of axons.